Absence of high‐risk stigmata predicts good prognosis even in severely anemic patients with suspected acute upper gastrointestinal bleeding. Issue 5 (1st June 2018) - Horibe, Masayasu; Ogura, Yuki; Matsuzaki, Juntaro; Kaneko, Tetsuji; Yokota, Takuya; Okawa, Osamu; Nakatani, Yukihiro; Iwasaki, Eisuke; Nishizawa, Toshihiro; Hosoe, Naoki; Masaoka, Tatsuhiro; Yahagi, Naohisa; et al.
Abstract : Background: The need for a blood transfusion, defined as hemoglobin < 70 g/L, is the measure for assessing the risk levels in patients with upper gastrointestinal bleeding (UGIB). However, not all patients with a low hemoglobin level have a poor prognosis. Objective: We assessed the clinical predictive factors associated with poor short‐term prognosis in patients with a low hemoglobin level. Methods: In this prospective cohort study, all consecutive patients with suspected acute UGIB at Tokyo Metropolitan Tama Medical Center were enrolled between 2008 and 2015. Then, we extracted those who needed a blood transfusion (hemoglobin < 70 g/L) and explored the variables associated with all‐cause mortality within 28 days after presentation. Results: Among 1307 patients, 311 needed a blood transfusion and 13 (4.2%) died from all causes. The presence of high‐risk stigmata requiring endoscopic treatment (peptic ulcers; Forrest scores Ia, Ib and IIa; varices with current bleeding or signs of recent bleeding; and spurting or gushing bleeding or visible vessel in other diseases), diagnosed by emergency endoscopy, was a unique factor affecting mortality (odds ratio: 8.47, 95% confidence interval: 1.45–160, P = 0.01). Patients without high‐risk stigmata neither died from UGIB nor had rebleeding, irrespective of the hemoglobin levels. Conclusions: Patients without high‐risk stigmata showed a good prognosis even if they needed a blood transfusion. This result could facilitate triage of patients with suspected acute UGIB who only need a blood transfusion.